Heavy Metal Emitting from Welding Fumes in automative Industry - Norhidayah, Abdull (Excellent Publisher, 2015)
Heavy metal emitting from welding fumes in the automative industry provide the significant health impacts to workers. Objectives of this study was to investigate the characteristics of the occupational environment setting in an automotive industry, to study the concentration of heavy metals in the welding fumes and to propose the appropriate control measure of welding fumes emission toward safe works environment in an automotive industry. A personal monitoring and area monitoring was conducted to determine the workers exposures to welding fumes.The concentration of welding fumes was analyzed by using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS)with referring to ASTM. All the heavy metals were permitted the OSHA PEL-TWA except Arsenic. The appropriate control measures was proposedsuch as substitution and local exhaust ventilation which towards safe and healthy environment.